Remembering Our Past: Reconstructing the Field of Canadian Communication Studies - Robinson, Gertrude J. (Canadian Journal of Communication, 2000)
Doing a historiography of the field of Canadian communication studies is very much a work in progress for which many of the building blocks are not yet known. Three types of information are needed. Information on the sociohistorical setting in which our field emerged, on the founders who conceptualized it in different universities (French and English), and on the theoretical emphases of our field. This paper brings together some of this contextual evidence.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMjIyMzAvY2pjLjIwMDB2MjVuMWExMTQ1